Deradicalization Strategy: Correcting Terrorist Inmates’ Understanding of the Implementation of Islamic Law in Indonesia - Nahrowi; Masyrofah; Irfan, M. Nurul; Prawiro, Atmo (Hikmatuna : Journal for Integrative Islamic Studies, 2025)
The deradicalization program in Indonesia has yet to achieve its intended goal of halting the spread of radical terrorist ideologies. This article explores a deradicalization strategy focused on Islamic religious perspectives concerning the application of Islamic law in Indonesia, specifically targeting terrorist inmates at a correctional facility located in Sentul, Bogor. Data were collected through interviews and document analysis. This study finds three core elements are instrumental in the deradicalization strategy aimed at correcting inmates’ misperceptions of Islamic law enforcement in Indonesia through religious education: instructional content, instructors/facilitators, and teaching methodologies. Elements from Islamic law and the Indonesian legal system positively contribute to the curriculum, serving as educational material for instructors. The content provided is in-depth and addresses fundamental Islamic legal concepts integrated with Indonesia's prevailing legal framework. As a result, terrorist inmates can gain a more comprehensive and integrated understanding. However, the current curriculum does not adequately cover the legislative application of Islamic law in Indonesia through statutory regulations, necessitating its ongoing development and periodic revision. There is also a shortage of qualified personnel capable of integrating and effectively communicating both Islamic legal principles and Indonesian law in a factual and comprehensible manner. An integrated understanding of Islamic religious perspectives and national identity is essential to align inmates’ knowledge with the legal application of Islamic law in Indonesia. Furthermore, the limited understanding among terrorist inmates regarding Indonesia's legal system and democratic governance has led to the erroneous belief that Indonesia is not a country that applies Islamic law.